The Application of Management Information Systems and Digital Transformation in Chicken Crunchy Roll MSMEs to Improve Operational Efficiency and Data Security - Jelita Jurniarti; Fauzan Yanuardi; Putri Nurlaila Azizah (Takaza Innovatix Labs Ltd., 2026)
This study aims to provide an example of the application of a Management Information System (MIS) and digital transformation in the Micro, Small, and Medium Enterprise (MSMEs) Chicken Crunchy Roll, which previously operated using manual methods. This effort is intended to improve operational efficiency, data security, and financial information management within the enterprise. The study employs a descriptive qualitative approach through observation and direct interviews with the business owner to obtain an overview of the enterprise’s condition and its MIS implementation. The results indicate that financial recording at Chicken Crunchy Roll MSMEs is still conducted manually and not performed on a regular basis. However, the enterprise has utilized social media, specifically Instagram, as a promotional tool, and adopted QRIS-based digital payments for non-cash transactions. The owner has not yet implemented a point-of-sale (POS) application or cloud computing technology, which limits the business’s ability to manage data efficiently and streamline administrative processes. The implementation of an MIS is considered capable of enhancing operational effectiveness, data protection, and the accuracy of financial reporting. Therefore, it is necessary to develop digital transformation strategies for MSMEs to enable adaptation to technological changes and strengthen their competitive advantage.